Key Success Factors in Managing and Implementing Public Funded R&D Projects in Indonesia - Wati Hermawati (STI Policy and Management Journal, 2020)
Public Research Centers (PRCs) in Indonesia are mostly operated by government funding. However, their role in supporting innovation and economic performance of MSMEs (micro, small and medium enterprises) is still very small.  The objective of this research is to determine what are the success factors in managing R&D projects at a PRC in Indonesia, particularly in providing solving problems of MSMEs. Two case studies of R&D Projects from a PRC ‘X’ were selected, namely: organic fertilizer project and appropriate technology project.  Both projects are quite different in terms of the research process. By using qualitative method, all R&D process elements were investigated. Results of the study shows that in general both case studies have indicated success factors that make R&D project success and effectively manage and grouped them into three common categories, namely project management process; project resources;  and project environments. The two case studies show that each project have different success factors and the lessons learned of these projects can be very useful to improve R&D project activities at PRCs.Keywords : R&D Project, Public Research Center, Success Factors, R&D Management